Experimental investigation on the effect of inlet swirl generator on heat transfer and pressure drop of non-Newtonian nanofluid. (25th January 2019) - Taheran, Ehsan; Javaherdeh, Kourosh
Highlights: Viscosity and thermal conductivity of non-Newtonian nanofluid are measured and modeled. Heat transfer, pressure drop and decaying rate of a swirl flow are investigated. Convective rate and pressure drop have increased by more twisted swirl generators. Thermo-hydraulic performance of swirl flow generators is evaluated and discussed. Abstract: Experimental study has been carried out to investigate the effects of inlet swirl generator on heat transfer and pressure drop of non-Newtonian drilling nanofluid under turbulent flow conditions. The equal volume mixture of water base silver nanofluid and a biological oil diluted by water was used as under test fluid. Thermal conductivity and rheological properties of novel drilling nanofluid were measured and an empirical model for thermal conductivity was proposed. Non-Newtonian power law coefficients of drilling nanofluid at three different temperatures were also presented. Nusselt number and friction factor for three different swirl generators twist angle (θ = 120 °C, 240 °C and 360 °C) were evaluated and thermo-hydraulic performance of non-Newtonian drilling nanofluid ( ∅ = 0.1 %, 0.5 % a n d 1 % ) was calculated at different Reynolds numbers from 4, 000 to 10, 000. The obtained results stated that the flow behavior depends on the nanofluid concentration, swirl generators geometry and Reynolds number. According to the experimental data, Nusselt number increased up to 86% but enormous enhancement in friction factor (up to 370%) limited the maximum thermo-hydraulic performance augmentation to 35%.